2013
DOI: 10.13076/j.tjo.2013.26.01_1
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Predictability of Maxillary Advancement and Impaction in Le Fort I Osteotomy

Abstract: Objective: The aim of this study was to evaluate and compare the amount of preoperatively planned surgical movement of the maxilla and postoperatively obtained maxillary repositioning. Materials and Method: Thirty-one patients (16 female and 15 male) were included in this study. Fifteen combined maxillary advancement and impaction, 5 isolated maxillary impaction, and 11 isolated maxillary advancement surgeries were performed by the same surgical team. The 31 patients were divided into 2 groups: group 1 (GoGnSN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…They found that the maxillary impaction movement could be estimated with a margin of error of 1 mm at a rate of 35% in the posterior region and 51% in the anterior region. They also reported that maxillary advancement movement could be estimated with an error margin of 2 mm (51%) and 1 mm (29%) 16). In our study, the amount of movement and lateral cephalometric radiographs before and after the operation were registered using Dolphin Imaging software.…”
Section: Discussionmentioning
confidence: 94%
“…They found that the maxillary impaction movement could be estimated with a margin of error of 1 mm at a rate of 35% in the posterior region and 51% in the anterior region. They also reported that maxillary advancement movement could be estimated with an error margin of 2 mm (51%) and 1 mm (29%) 16). In our study, the amount of movement and lateral cephalometric radiographs before and after the operation were registered using Dolphin Imaging software.…”
Section: Discussionmentioning
confidence: 94%